Autonomía de la mala práctica médica como delito contra la vida - Suárez Jurado, Carla Natalia (2011)
The interrelationship of people is an inevitable consequence of the society, individuals develop activities that satisfy the necessities of the others, and that is how people improve their quality of life. Along human being history, not only societies but also activities have changed, creating new situations that werent expected and need to be regulated because they can cause damage in humans. Medicine is one of those activities that has changed. Around the world many countries had regulated the medicine science it has produced harmful effects on people becoming a medical malpractice act. The medical malpractice act entered the Criminal Law sphere when it was cataloged by many jurisdictions around the world as a reckless crime. These jurisdictions have analyzed the different theories of the felony, concluding that Functionalist Theory is the most appropriate to analyze the crime and that objective imputation is the best way to punish the medical malpractice act. Ecuador is not exempt of medical malpractice acts, but sadly, this country doesnt have any law or regulation that handled these types of acts in a right way. To fill this lack of regulation there is a proposal of a specific criminal offense that contains the evaluative elements of the crime that are explained on the Objective Imputation Theory and solves the medical malpractice issue. The creation of this specific criminal offense is supported on the fact that the use of similar crimes such as unintentional murder or unintentional injury doesnt solve the problem of a medical malpractice act. Instead, it entails a degree of impunity because these acts are punished in an inappropriate way or not punish at all.